2018
DOI: 10.1002/jmv.25027
|View full text |Cite
|
Sign up to set email alerts
|

What is changed in HBV molecular epidemiology in Italy?

Abstract: Hepatitis B virus (HBV) infection represents the most common cause of chronic liver diseases worldwide. Consequently, to the introduction of the universal HBV vaccination program, the prevalence of hepatitis B surface antigen was markedly reduced and less than 1% of the population of Western Europe and North America is chronically infected. To date, despite great advances in therapeutics, HBV chronic infection is considered an incurable disease. Ten hepatitis B virus genotypes (A-J) and several subgenotypes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 98 publications
1
6
1
Order By: Relevance
“…In children, its effectiveness exceeds 90% and, comparing the era before vaccination and 2015, the WHO reported that global coverage with the three doses of hepatitis B vaccine in infancy reached 84% in 2015 and resulted in a decrease in the global proportion of children under 5 from 4.7% to 1.3% [136]. Moreover, the prevalence of HBsAg was markedly reduced and less than 1% of the population of Western Europe and North America is chronically infected [104].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, its effectiveness exceeds 90% and, comparing the era before vaccination and 2015, the WHO reported that global coverage with the three doses of hepatitis B vaccine in infancy reached 84% in 2015 and resulted in a decrease in the global proportion of children under 5 from 4.7% to 1.3% [136]. Moreover, the prevalence of HBsAg was markedly reduced and less than 1% of the population of Western Europe and North America is chronically infected [104].…”
Section: Discussionmentioning
confidence: 99%
“…To test HBsAg in blood donors, a oneyear study from April 2004 to March 2005 was performed on 31,190 Italian volunteer blood donors from age classes not subjected to universal HBV vaccination of which 100 (0.32%) were positive for both HBsAg and anti-HBc and two for HBsAg (0.01%) alone, suggesting a prevalence rate for HBV infection of 0.33% [103]. More recently, the rate of HBsAg-positive subjects in the open population ranged between 0.8% and 1% [104]. In Italy, prevalence of HBV infection in HD patients ranges from 0.6 to 2.2%, despite the decline of HBV infection worldwide in the general population, according to data from Regional Italian Registries.…”
Section: Preventionmentioning
confidence: 99%
“…Of note, for 72.1% of them the diagnosis was late and less than 6 months prior to developing AIDS 3 . Concerning HIV most frequent co-infections, while the relative proportion of immigrants with chronic HBV infection in Italy has been estimated to be 20% 4 , the relative proportion of HCV infected immigrants is small 5,6 . Finally, a wide study in a cohort of over 27,000 socially marginalized immigrants in Piedmont estimated a prevalence of 2.7% of active TB 7 .…”
mentioning
confidence: 99%
“…In the last few decades, the increasing incidence of HCC is ascribed to the emergence of chronic liver disease due to HCV and NAFLD but also to an increase in HBV-related HCC, particularly among immigrants from countries with endemic HBV infection. About half of HCC is related to alcohol consumption in Central and Eastern Europe, and to HCV in Western Europe [50] . The proportion of HBV-related HCC is about 15%-20% across different European countries and seems to be more frequent in Eastern Europe and combined with HCV or HDV co-infection [49] .…”
Section: Europementioning
confidence: 99%